Methodological-didactic teacher education in Italian secondary school and competence assessment1 - Santis Cristiana De; Carruba Maria Concetta; Martiniello Lucia (Research on Education and Media)
The paper aims to reflect on the training of teachers in Italian lower and upper secondary schools by presenting the training activities carried out by the Pegaso Telematic University in the provision of the training course foreseen by Ministerial Decree 180/2022. The first training activities focused on the training of the course tutors, while the second focused on the feedback given to the teachers who followed the course, following the development of the competence assessment. The aim of this paper is to reflect on the replicability of the training actions presented and the lines of research that open up.